Synthesis of Linear α,β-Unsaturated Amides from Isocyanates and Alkenylaluminum Reagents - Chen, Bo; Wu, Xiao-Feng (Synlett, 2020)
A new approach has been developed for the synthesis of linear α,β-unsaturated amides by the direct coupling of isocyanates with alkenylaluminum reagents. At room temperature, the desired α,β-unsaturated amides were isolated in good to excellent yields with good functional-group tolerance in the absence of any catalyst or additive.
Keywords: enamides; alkenylaluminum reagents; isocyanates; coupling reaction; catalyst-free